Migration and medicine - Steger, Florian; Orzechowski, Marcin; Rubeis, Giovanni; Schochow, Maximilian (Verlag Karl Alber, 2021)
In the summer of 2015, a strong migration movement towards Europe set in. This led to ethical, legal and societal challenges in the medical care of the refugees. These included cultural conflicts in medical practice and deficits in the institutional handling of cultural diversity. The book analyzes different challenges and offers possible solutions.
Keywords: Konferenzschrift -- Ulm -- 2019; Medizinische Ethik; Medizinische Versorgung; Flüchtling; Interkulturalität; Medizin; Gesundheitswesen; Flucht; Migration